Mammography and Pap smear use by older rural women. - Ives, Diane G.; Lave, Judith R.; Traven, Neal D. (Public Health Reports)
The use of mammograms and Pap smears by rural, older, community-dwelling women in the first 2 full years these services were covered by Medicare was investigated. Although the National Health Interview Survey and other studies have indicated that there is an increase routine screening mammography and Pap smears, a lot of women are still not undergoing these tests. Medicare claims data from 1991 and 1992 were analyzed for 2,205 women who were aged 65–79 years, resided in 1 of 5 participating rural Pennsylvania counties, and were covered under Part B of Medicare. Of 2,175 women still living after 3 years, 44.6 percent had undergone mammography and 14.6 percent had undergone a Pap smear in either 1991 or 1992. In general, women who were older, less educated, unmarried, and poorer were less likely to have mammograms and Pap smears. As financial cost is now less of an obstacle, more aggressive attempts must be made to persuade older women to undergo these 2 tests.